Islamic State Khorasan Province (ISK): An Imminent Threat for Central Asia and Beyond - Ivaylo Tasev (Bulgarian Journal of International Economics and Politics)
This study examines the Islamic State Khorasan Province (ISK), a terrorist organization operating primarily in Central Asia, with a particular focus on Afghanistan and Pakistan. As a regional affiliate of the Islamic State of Iraq and Syria (ISIS Central), which was militarily defeated in 2019, ISK continues to orchestrate lethal attacks across Central Asia and beyond, posing an ongoing security threat. It perceives multiple entities, including the Taliban, Al-Qaeda, and Western powers, as adversaries. While ISK inherits the ideological framework of ISIS Central, it has strategically diverged by adopting a guerrilla warfare approach. This research aims to analyse the distinctions between ISIS Central and ISK, specifically in terms of their objectives and operational strategies. The central hypothesis posits that ISK’s tactical and ideological deviations stem from contemporary geopolitical conditions and its unique organizational dynamics. Methodologically, this study employs qualitative research, drawing upon secondary sources to examine ISK’s evolution. In addition, it employs a case scenario methodology to assess the evolving threat posed by the ISK to Central Asia and beyond. The findings indicate that Wilayat Khorasan represents the most extreme manifestation of Islamic jihadism and is widely regarded as the most dangerous ISIS affiliate in the present era.